Study Of Nutrient Potential Waste Of Catfish, Cow Dung, And Ketapang Leaves As Solid Organic Fertilizer (POP) - Oto Prasadi; Nurlinda Ayu Triwuri (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
Aquaculture will produce waste in the form of manure and there are many ketapang trees whose leaves fall that can be used as a material for making green fertilizer. The purpose of this study was to determine the nutrients, i.e. nitrogen, phosphorus, potassium, C-organic, C/N ratio and pH in solid organic fertilizer (POP) from fish waste water, cow dung and ketapang leaf compost. Fish solid waste is taken from the harvest pond that has been stirred and filtered, while for cow dung and ketapang leaves using the addition of a bioactivator (EM4 + molasses), with treatment (dried ketapang leaves: cow dung: bioactivator) P1 (1 kg : 0.25 kg : 250 ml), P2 (0.875 kg : 0.375 kg : 250 ml) P3 (0.75 kg : 0.5 kg : 250 ml), control (1.25 kg : 0 kg : 250 ml). Composting was carried out anaerobically with a composting time of 28 days. Based on the research results only C-organic and pH of all types of fertilizers as well as C/N ratio of cow dung and ketapang leaves, total phosphorus from fish waste that meets the requirements of the Ministry of Agriculture 70 of 2011, concerning POP, it must contain a minimum NPK of 4%, pH 4-9, C-organic at least 15% and a C/N ratio of 15-25%, while according to the compost standard SNI-19-7030-2004, the levels of nitrogen at least 0.4%, phosphorus at least 0.1%, potassium at least 0.2%, C-organic 27-58% and C/N ratio 10-20%.